1976
DOI: 10.1063/1.432638
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen abstraction reactions by atomic fluorine. V. Time-independent nonthermal rate constants for the 18F+H2 and 18F+D2 reactions

Abstract: The general time-independent collision theory formulation for the bimolecular rate constant has been adapted for the description of hot atom systems. Two types of hot atom energy distribution functions have been considered in an application to the 18F+H2 reaction system: (i) a δ-function distribution, and (ii) a steady-state Maxwellian distribution characterized by a hot atom temperature TA. From the time-independent solution of the Boltzmann equation together with microscopic reactive cross sections determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Under favorable circumstances reactive collision energy Information can be obtained from hot atom mixture experiments [13,19,20,[32][33][34][35][36][37]. Both inert and reactive additives may induce changes in the secondary product distributions that accompany energetic '*F substitution reactions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under favorable circumstances reactive collision energy Information can be obtained from hot atom mixture experiments [13,19,20,[32][33][34][35][36][37]. Both inert and reactive additives may induce changes in the secondary product distributions that accompany energetic '*F substitution reactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown that Information concerning the energy ränge characteristics of nonthermal reactions is difficuh, if not impossible, to obtain from conventional moderator experiments [14,16,17]. In the present study the influence of Ar additive upon the dynamical and energetic features of the nonthermal + Hj reaction [19][20][21][22][23] has been elucidated with the aid of the steady State kinetic theory of hot atom reactions [21,24,25]. This work represents the first adaptation of the steady State theory for modeling a mukicomponent reaction system.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations